Autism Spectrum Disorder: FRAXE Mutation, a Rare Etiology - Correia, F (2014)
Autism spectrum disorder (ASD) is characterized by impaired social interaction and communication, restricted interests and repetitive behaviors. Fragile X E is associated with X-linked non-specific mild intellectual disability (ID) and with behavioral problems. Most of the known genetic causes of ASD are also causes of ID, implying that these two identities share common genetic bases. We present a child with an ASD with a normal range of intelligence quotient, that later evolved to compulsive behavior. FRAXE locus analysis by polymerase chain reaction revealed a complete mutation of the FMR 2 gene. This report stresses the importance of clinicians being aware of the association between a full mutation of FMR2 and ASD associated with compulsive behavior despite normal intellectual level.